Students Legal Awareness of The Prohibition of Online Gender-Based Violence (Study at Faculty of Law, Universitas Jenderal Soedirman) - Nandita Uttami, Shakira; Lisiani Prihatinah, Tri; Musyahadah Rahmah, Alef (Jurnal Hukum In Concreto, 2024)
This research aims to determine the level of students' legal awareness regarding the prohibition of Online Gender-Based Violence as well as the influence of disciplinary factors, socialization intensity factors, and religious piety factors on students' legal awareness regarding the prohibition of Online Gender-Based Violence at the Faculty of Law, Jenderal Soedirman University. This research uses quantitative research methods with a sociological juridical approach and descriptive research specifications. Types and sources of data include primary data and secondary data obtained using questionnaire, documentary and library methods. The research results show that the level of legal awareness of students regarding the prohibition of Online Gender-Based Violence at the Faculty of Law, Jenderal Soedirman University is high. This is proven by the results of research on 4 (four) indicators including the high level of student legal knowledge, the high level of student legal understanding, the number of students' legal attitudes that agree, and the number of students' legal behavior that is in accordance with the prohibition of Online Gender-Based Violence. Discipline factors, socialization intensity factors and religious piety factors have a positive influence on students' level of legal awareness regarding the prohibition of Online Gender-Based Violence.